Newer modalities for treatment of severe COVID-19 infection and their use in pregnancy-boon or bane? - Anand, Shivani; Sarkar, Avir (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
We are into the second year of the COVID-19 pandemic which is caused by an RNA virus, belonging to the severe acute respiratory syndrome (SARS) family. Though the mainstay of COVID management continues to be mainly symptomatic, many new management options are coming up. Due to ethical reasons, pregnant and lactating women are never included in the clinical trials used to test drug safety and efficacy, but COVID-19 is here to stay and we should begin to analyse the effects of the various proposed drugs in its management in pregnant population.